A Case of Matricidal Schizophrenia - Çakıcı, Mehmet; Çakıcı, Ebru; Ataklı, Cem; Arkonaç, Oğuz; Polat, Oğuz (The Bulletin of Legal Medicine, 1996)
Although murdering one’s mother is a subject that has been discussed in many case reports, it is not easy to explain the mechanisms and motivations involved. In this case report we present a man diagnosed as paranoid schizophrenia acording to DSM-IV criteria who murdered his mother, injured four people and jumped from the window of the third floor after shoting his foot fingers. Most of the matricidal studies show common characteristics of matricidal men. Matricidal men mostly use excessive violence and kill their mothers in their bedrooms. They are usually the youngest child and have ambivalant attachment to their mothers like in our case. In this case report characteristics of matricidal schizophrenics is discussed in the ligth of a psychotic man who not only perceived his mother as a threat to his existence but also had protection and rescue feelings for her because of excessive love. Key words: Matricide, Schizophrenia